Green Synthesis, Characterization and Optimization Studies of Zinc Oxide Nano Particles Using Costusigneus Leaf Extract. (2018) - Chinnasamy, C.; Tamilselvam, P.; Karthick, B.; Sidharth, B.; Senthilnathan, M.
Abstract: In the present study, a green approach was applied for synthesis of zinc oxide Nano particles using CostusIgneus leaf extract. The CostusIgneus leaves act as both reducing and capping agent and helps in synthesizing zinc oxide nanoparticles. The parameters which are influencing the yield of synthesis process are identified and optimized by choosing different levels in each parameter using Design of Experiments L9 orthogonal array. The ZnO nanoparticles were synthesized using the optimum combination of parameters and then characterization studies are carried out using Ultra Violet-Vis spectroscopy, Fourier Transform Infrared Spectroscopy and X-Ray Diffraction. Further, the morphological studies are conducted using Scanning Electron Microscope and Energy Dispersive X-ray spectroscopy. The characterization results confirm the formation of ZnO Nano particles and the particle size are found to be 31 nm and spherical in shape. The green synthesis process is found to be one of the simple and economic method, less time consuming, eco-friendly and does not require any hazardous chemicals.